Analysis of Adjectives in Headline News Online - Hermariyanti Kusumadewi; Ferawaty Puspitorini (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
The purpose of this study is to analyze the adjectives in headline news online; to answer questions such as: How many adjectives that can be found in headline news online? What kind of adjectives that are widely used in headline news online? The data in this study were collected from headline news online. Literature review and relevant research has been observed to obtain a description of the data, in this case headline news online. The results showed that the author of the article using different types of adjectives, the adjectives most often used is a descriptive adjective. The main reason of the research on the analysis of adjectives in headline news online is to provide information on headline news online that can be read on the internet, and provide benefits in the study of language. Key words: adjective, headline news online, reading habit